Democracies in Conflict: The Role of Public Opinion, Political Parties, and the Press in Shaping Security Policy. (October 2017) - Gelpi, Christopher
The vast literature on the impact of democratic political institutions on foreign policy behavior has yielded some of the most important developments in our understanding of violence and war over the past thirty years. The Journal of Conflict Resolution has played a prominent role in this growth and development. Critics of the democratic peace have dismissed this literature as a correlation in search of an explanation. However, I argue that the democratic peace literature and its various descendants represent a surprisingly productive example of an empirically focused and puzzle-oriented research program that has produced cumulative scientific knowledge regarding our understanding of international politics. This sustained investigation of democracy and foreign policy has yielded an increasingly robust and sophisticated model of democratic constraint that is the consequence of a progressive research program that compares favorably to earlier research programs that emphasized clashing paradigms of international politics.